Biodistribution of orally administered 99mTc-heparin to assess eosinophilic esophagitis associated inflammation. (November 2019) - Saffari, Hedieh; Condie, Russell M.; Watson, Brian R.; Krstyen, Jeffrey J.; Peterson, Kathryn A.; Hoffman, John M.; Gleich, Gerald J.; Pease, Leonard F.
Graphical abstract: Highlights: Analysis of 99m Tc-heparin conjugate transport throughout the gastrointestinal tract. Conjugate detects eosinophil associated inflammation. No animal model for degranulating eosinophils so mathematical modeling essential. Reaction-diffusion model informed by binding kinetics to non-human primate tissue. Radiopharmaceutical remains within the gastrointestinal tract in mouse model. Abstract: Here we explore the biodistribution of 99m Tc-heparin, an orally administered radiopharmaceutical candidate expected to identify localized inflammation in eosinophilic esophagitis (EoE). Heparin binds to eosinophil granule proteins in inflamed regions of gastrointestinal (GI) organs, and 99m Tc signals their location. This article evaluates the biodistribution of this conjugate first within the esophagus by modeling the reactive transport of 99m Tc-heparin based on the kinetics of 99m Tc-heparin binding to non-human primate esophagi and second in the remainder of the body by measuring organ specific uptake using single-photon emission computed tomography/computed tomography imaging. Results show that binding and dissociation rate constants remain similar, and that optimal imaging occurs after drinking of the agent is complete. We also find that 99m Tc-heparin remains within the GI tract simply transporting through the gut and out. These findings provide a new avenue to clinically explore the utility of 99m Tc-heparin to detect eosinophil associated inflammation in the GI tract.